Skill Development Courses in Physics - Kakade, Sandip G. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Physics itself covers a broad area in academics and science, so the subject itself is having big opportunities to start the skill development courses related with the different fields in physics. Moreover, the student’s interest plays a crucial role and need to be considered while offering the skill development course to the students. In this paper, I have discussed the skills gained by the students during the learning of basics of physics including experimental physics and the probable startup of skill development courses accordingly. I have explained the importance of different stages like title of the course, designing of curriculum of the skill development course, importance of skill development in applications of the course and placements and also missing part from the current theoretical syllabus which plays the crucial role in achieving the skills. I also have explained some new skill development courses. The significant possible skills are discussed in the paper for the students. This paper will be helpful to start the skill development courses for the physics students for their future scope in the current scenario as per the guidelines of national education policy for the student’s benefits.